Environmental plant physiology - Willey, Neil
Environmental Plant Physiology focuses on the physiology of plant-environment interactions, revealing plants as the key terrestrial intersection of the biosphere, atmosphere, hydrosphere and geosphere. It provides a contemporary understanding of the topic by focusing on some of humankind's fundamental biological, agricultural and environmental challenges. Its chapters identify thirteen key environmental variables, grouping them into resources, stressors and pollutants, and leading the reader through how they challenge plants and how plants respond at molecular, physiological, whole plant and ecological levels. The importance of taking account of spatial and temporal dimensions of environmental change in order to understand plant function is emphasised. The book uses a mixture of ecological, environmental and agricultural examples throughout in order to provide a holistic view of the topic suitable for a contemporary student audience. Each chapter uses a novel stress response hierarchy to integrate plant responses across spatial and temporal scales in an easily digestible framework.